Research progress on factors influencing suboptimal immune reconstitution in HIV infection: a systematic literature review - Wei CHEN; Qiuyi YANG; Xiaoliang ZENG (Zhongguo gonggong weisheng)
Acquired immunodeficiency syndrome (AIDS) is an immunodeficiency syndrome caused by infection with the human immunodeficiency virus (HIV). Currently, antiretroviral therapy (ART) is the primary method for treating and managing HIV infection. With the widespread use of ART, the HIV virus is suppressed, the body′s immune function gradually recovers, and the morbidity and mortality of HIV-related diseases are significantly reduced. However, some patients still fail to restore their immune function to a normal state even after long-term, regular, and effective ART, a phenomenon known as immune non-response (INR). To date, the underlying mechanisms of INR in HIV-infected patients have not been fully elucidated, but studies have shown that multiple factors may be involved. This article reviews the influencing factors of INR through an extensive literature review to provide clinical references for improving INR in HIV/AIDS patients.